Surgical complications: a hospital-wide registering system and factors associated with surgical complications - Saarinen, Ira (fi=Turun yliopisto|en=University of Turku|, 2023)
ABSTRACT The primary aim of the present thesis was to study how surgical quality can be measured in a single hospital, by creating and describing a simple and usable tool for registering outcomes data based on severity of complications. First, a systematic review of the subject was conducted. The evaluation of the articles revealed wide methodological heterogeneity in the classification and categorization of complications and data collection methods. Subsequently, a pilot hospital-wide surgical complication register was created and implemented in Satasairaala, Pori, Finland. Perioperative data related to all adult general and orthopedic surgery procedures for 3 years (2016–2018) were included in the study. Complications were recorded according to a modified Clavien–Dindo classification, and the preoperative risk factors were compiled based on the literature and coded as numerical measures. The overall complication rate in 4529 patients was 17.2% (95% confidence interval (CI) 16.1–18.3), and 4.6% (95% CI 4.0–5.2) were graded as major complications. The results also showed that only a few patient-related risk factors were sufficient to account for the case mix. Further aims of this thesis were to study factors associated with patient education and patient perceptions on surgical quality, and their association with surgical complications. Adult patients undergoing surgical operations were studied by questionnaires in 2016–2017 in Satasairaala, Pori. The results indicate that the information needs of the patients vary individually. The level of received information by patient education and the patient perception on quality of care may have an association with reported surgical complications. KEYWORDS: surgery, quality improvement, health policy, health services management, performance measures, quality in healthcare, patient safety, human resource management, human factors, real-world effectiveness

TIIVISTELMÄ Tämän tutkimuksen ensisijaisena kohteena on kirurgisten komplikaatioiden mittaaminen sairaalatasolla. Väitöskirjan tavoitteena oli luoda kaikki kirurgian alat kattava komplikaatioita mittaava rekisteri, joka hyödyntää olemassa olevaa sähköistä sairaskertomusjärjestelmää. Järjestelmällisen katsauksen avulla selvitettiin ensin tieteellisessä kirjallisuudessa julkaistut tutkimukset olemassa olevista vastaavista rekistereistä sekä ne potilaaseen ja kirurgiseen toimenpiteeseen liittyvät tekijät, joiden tiedetään olevan yhteydessä kirurgisiin komplikaatioihin. Järjestelmällinen kirjallisuuskatsaus osoitti, että tiedonkeruumenetelmissä ja komplikaatioiden luokittelussa on maailmalla suurta vaihtelua. Satasairaalaan luotiin pilottihankkeena koko kirurgian klinikan laajuinen komplikaatiorekisteri, ja tässä väitöskirjassa esitellään tulokset kolmen vuoden ajalta (2016–2018). Komplikaatioita todettiin 17.2 %:lla (95 %CI 16.1–18.3) 4529 leikatusta potilaasta. Näistä 4.6 % (95 %CI 4.0–5.2) luokiteltiin vakaviksi. Tulosten mukaan potilaskohtaisen riskin määrittämiseen saattaa riittää muutama kliininen mittari. Lisäksi tässä väitöskirjassa tutkittiin, missä määrin potilaan informointi ja ohjaus sekä potilaan kokemus hoidon laadusta ovat yhteydessä komplikaatioiden esiintyvyyteen kotiutuksen jälkeen. Tulosten mukaan potilaskohtaisen ohjauksen tarve vaihtelee yksilöllisesti, ja potilasohjauksella ja potilaan kokemalla laadulla saattaa olla yhteyttä leikkauksesta toipumiseen ja komplikaatioiden esiintymiseen. Tässä väitöskirjassa kuvataan koko aikuiskirurgian kattava komplikaatioita mittaava järjestelmä, sekä tuodaan esiin kirurgisen hoidon osa-alueita, joilla saattaa olla yhteyttä hoidon lopputulokseen, esimerkkeinä potilasohjaus ja potilaan kokema laatu. AVAINSANAT: kirurgia, laadun parantaminen, terveyspolitiikka, terveydenhuoltohallinto, dokumentointi, potilasturvallisuus, terveydenhuollon laatu, henkilöstöhallinto, inhimilliset tekijät, arkivaikuttavuus